Pengaruh Harga dan Atmosfer Toko terhadap Keputusan Pembelian Ulang yang Dimoderasi Kepuasan Pelanggan: (Studi pada Konsumen Beocca Coffee Kabupaten Malang) - Akhmad Samsu Rijal; Survival Survival; Mulyono Mulyono (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study aims to examine the influence of price and store atmosphere on repurchase decisions, with customer satisfaction as a moderating variable among Beocca Coffee consumers in Malang Regency. A quantitative explanatory approach was employed, involving 130 respondents selected through purposive sampling. Data were collected via an online questionnaire and analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM). The results show that price, store atmosphere, and customer satisfaction have a positive and significant effect on repurchase decisions. However, customer satisfaction was not proven to moderate the relationship between price and repurchase decisions, nor between store atmosphere and repurchase decisions. These findings indicate that price and store atmosphere influence repurchase decisions directly, regardless of customer satisfaction levels. The practical implication is that coffee shop managers should focus on offering competitive prices and creating a pleasant store atmosphere. Although customer satisfaction does not act as a moderator, it remains a crucial direct factor affecting loyalty. Future studies are encouraged to expand the research scope geographically and include additional variables such as customer loyalty, perceived quality, or digital marketing strategies to deepen the understanding of repurchase behavior in the local coffee shop industry.